Express method for contactless measurement of parameters of thermoelectric materials - Ashcheulov, A. A.; Buchkovskii, I. A.; Romanyuk, I. S. (Technology and design in electronic equipment, 2015)
The paper presents an original method for contactless express measurement of parameters of thermoelectric materials.The presence of a combination of AC and DC magnetic fields in the gap of the oscillating circuit, where the monitored sample of the thermoelectric material is located, leads — due to Ampere force — to delamination of geometric regions of the occurrence of half-cycles of Foucault current. This in turn causes the appearance of additional heat losses in the oscillating circuit caused by Peltier effect.Computer modelling of these processes with the use of the software package ComsolFenlab 3.3 allowed determining the nature and magnitude of the electric currents in oscillating circuit, the range of operating frequencies, and the ratio of amplitudes of the variable and fixed components of the magnetic field. These components eventually cause a certain temperature difference along the controlled sample, which difference is proportional to the thermoelectric figure of merit of the material.The basic expressions are obtained for determining the value of the Seebeck coefficient, thermal conductivity, electrical conductivity and thermoelectric figure of merit.A description is given to the design of the device for contactless express measurement of parameters of thermoelectric materials based on Bi – Te – Se – Sb solid solutions. Its distinctive feature is the ability to determine the symmetric and asymmetric components of the electric conductivity of the material values. The actual error in parameter measurement in this case is 2%.